2009
DOI: 10.1103/physrevlett.102.118103
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Magnetic Surface Swimmers

Abstract: We report studies of novel self-assembled magnetic surface swimmers (magnetic snakes) formed from a dispersion of magnetic microparticles at a liquid-air interface and energized by an alternating magnetic field. We show that under certain conditions the snakes spontaneously break the symmetry of surface flows and turn into self-propelled objects. Parameters of the driving magnetic field tune the propulsion velocity of these snakelike swimmers. We find that the symmetry of the surface flows can also be broken i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
208
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(212 citation statements)
references
References 21 publications
1
208
0
3
Order By: Relevance
“…These challenges mean that most artificial microrobots actually have no actuators. Rather, they are in most cases rigid monolithic structures, either pushed by chemical reactions 15 or directly manipulated by torques or forces applied by external magnetic fields [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges mean that most artificial microrobots actually have no actuators. Rather, they are in most cases rigid monolithic structures, either pushed by chemical reactions 15 or directly manipulated by torques or forces applied by external magnetic fields [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…These challenges mean that most artificial microrobots actually have no actuators. Rather, they are in most cases rigid monolithic structures, either pushed by chemical reactions 15 or directly 4 manipulated by torques or forces applied by external magnetic fields [16][17][18][19][20] .Alternatively, they consist of flexible materials embedding, at best, a small number of passive degrees of freedom (DOFs) 21,22 .In macroscale robots, one approach to increase the number of DOFs has been to adopt soft bodies, capable of biomimetic actuation [23][24][25][26][27][28] . However, these approaches have resisted miniaturization.…”
mentioning
confidence: 99%
“…[17]) or by intrinsic self-propulsion mechanisms [18], opening the possibility for lane formation and related dynamical phenomena. Examples of swimmers with anisotropic (e.g., magnetic) interactions have been studied in [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, various artificial systems have been reported on, each showing interesting individual features. The systems can be categorized either as interface bound surfers [26][27][28][29], micro-machines [30][31][32], Janus particles [33][34][35][36][37] or active emulsions [38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%